Finite-time output feedback attitude control for rigid spacecraft under control input saturation. Issue 17 (November 2016) - Zou, An-Min; de Ruiter, Anton H.J.; Kumar, Krishna Dev
Abstract: In this paper, the problem of finite-time output feedback attitude control for rigid spacecraft subject to control input saturation is investigated. For the attitude stabilization, we propose a nonlinear finite-time observer using quaternion-based attitude representation. The estimated attitude of the observer always satisfies the unit norm constraint. The finite-time stability of the observer can be guaranteed by using homogeneous and Lyapunov methods. Furthermore, the effect of the external disturbance on the performance of the finite-time observer is analyzed. With the finite-time observer, we design an attitude stabilizing control law to guarantee that the attitude state of the spacecraft converges to the equilibrium point in finite time. We also discuss the finite-time attitude tracking control for spacecraft and propose a control scheme without requiring angular velocity measurements to guarantee that the desired attitude can be tracked in finite time. The main novelty of the control algorithms derived here lies in the fact that finite-time stability can be achieved even in the absence of angular velocity measurements as well as in the presence of constraints on control input magnitude. Numerical examples are presented to demonstrate the efficiency of the proposed control algorithms.